"BERTOLAK KE SEBERANG” SEBAGAI SIMBOL MELEWATI BATAS : TAFSIR TEOLOGI PEMBEBASAN ATAS MARKUS 4:35-41 - Viscka Eirene Daharang (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2025)
This paper explores the symbols of liberation in Mark 4:35-41 through the lens of liberation theology hermeneutics, with a particular focus on the phrase “let us go across to the other side” as an invitation to cross social, religious, and ideological boundaries. Jesus’ call to journey toward the non- Jewish region (the Decapolis) is interpreted as a gesture of liberation for the oppressed in the midst of Roman imperial dominance and the exclusivist structures of the Jewish community. The narrative of the Calming of the Storm reveals symbols of chaos shaped by oppressive political and structural systems. Reading Mark 4:35-41 through the perspective of liberation theology uncovers the universal scope of the proclamation of God’s Kingdom to the whole world. God is present amid suffering and oppression